GUIDANCE AND COUNSELLING: A QUALITATIVE APPROACH - Khanaya Noor Khalifah; Yasinta Sari Pratiwi (LP2M IAI Al-Khairat Pamekasan, 2026)
This research is motivated by the limitations of the quantitative approach in explaining the diversity of ways in which individuals experience and understand guidance and counseling practices in the context of education management. The complexity of the experiences of counselors, practitioners, and service participants demands a methodological approach that is able to capture variations in meaning systematically. The purpose of this study is to comprehensively explain phenomenography as a qualitative research approach and analyze the theoretical foundations, methodological principles, data collection procedures, analysis techniques, and reliability criteria relevant to guidance and counseling research. This study uses a qualitative approach based on literature review by critically analyzing the main scientific works on phenomenography and examples of their application in guidance and counseling research. The results of the study show that phenomenography is effective in identifying qualitative variations in the way individuals understand counseling phenomena through the development of hierarchically interconnected description categories, so as to be able to reveal the structure of the collective meaning of a phenomenon. The conclusion of this study confirms that the phenomenographic approach has a significant methodological contribution in enriching research and practice of guidance and counseling, particularly in supporting theory development, service quality improvement, and decision-making based on a deep understanding of human experience in education management.